2021
DOI: 10.3126/jpahs.v8i1.36858
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and attitude towards COVID-19 among nursing students of Lalitpur

Abstract: Introduction: Coronavirus disease 2019 (COVID-19) pandemic caused by a novel coronavirus mainly present with fever, dry cough, fatigue, myalgia, and dyspnea. This study was aimed to identify the knowledge and attitude toward COVID-19 among nursing students. Method: A cross-sectional analytical study was conducted to find out knowledge and attitude toward COVID-19 among nursing students of the School of Nursing and Midwifery, Patan Academy of Health Sciences, Lalitpur. Online Google form was used for data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
0
0
Order By: Relevance
“…According to their results, the general public in Libya had a clear understanding of COVID-19 and a favourable attitude toward it. This finding agrees with that of Shanti, et al (2021), who indicated that their study population had a positive attitude towards.…”
Section: Demographic Variables Of the Respondentssupporting
confidence: 92%
“…According to their results, the general public in Libya had a clear understanding of COVID-19 and a favourable attitude toward it. This finding agrees with that of Shanti, et al (2021), who indicated that their study population had a positive attitude towards.…”
Section: Demographic Variables Of the Respondentssupporting
confidence: 92%